2018
DOI: 10.1590/2317-1545v40n3198495
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance in Senna macranthera (DC. ex Collad.) H. S. Irwin & Barneby seeds with sodium nitroprusside (SNP) promoted by cyanide

Abstract: Studies show the positive effect of the nitric oxide donor in the seed germination process. However, there are no precise reports about which compound present in sodium nitroprusside would cause these effects in seeds under salt stress. The aim of this study was to evaluate the effects of SNP on germination of Senna macranthera seeds under salt stress. The osmotic potentials of -0.3, -0.4, and -0.5 MPa of NaCl were used, as well as the concentration of 100 μM of sodium nitroprusside, inactive sodium nitropruss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…These data corroborates studies carried out with the same specie (Silva et al, 2018) and where these substances are acting to bring about this recovery. In Arabidopsis a weakening of the root cell wall was observed 2-4 h after salt application (Feng et al, 2018), which could be facilitating the entry of the SNP and causing a greater efficacy when applied in conjunction (the stress saline and the donor).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These data corroborates studies carried out with the same specie (Silva et al, 2018) and where these substances are acting to bring about this recovery. In Arabidopsis a weakening of the root cell wall was observed 2-4 h after salt application (Feng et al, 2018), which could be facilitating the entry of the SNP and causing a greater efficacy when applied in conjunction (the stress saline and the donor).…”
Section: Resultssupporting
confidence: 88%
“…H. S. Irwin & Barneby, it was observed that the application of SNP in conjunction with saline stress is the best method to recover the germination of these seeds. These effects were similar to those brought about by the sodium nitroprusside treatment and were also observed in the treatments with inactive sodium nitroprusside and ferrocyanide, indicating that the effects observed were related to release of the cyanide present in the sodium nitroprusside (Silva et al, 2018).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is because salt stress limits water uptake by seeds, so without water uptake, the germination process is reduced or inhibited (Farooq et al 2017). The results of Silva et al (2018) highlight that salt stress delays germination and that the mechanisms involved need to be clarified in order to make a decision. As it is a weed, these strategies may be useful to adopt more efficient management and reduce the establishment of this species in crops.…”
Section: Resultsmentioning
confidence: 99%